1994
DOI: 10.1080/00071669408417703
|View full text |Cite
|
Sign up to set email alerts
|

Role of caeca in the nitrogen nutrition of the chicken fed on a moderate protein diet or a low rotein diet plus urea

Abstract: 1. A study was carried out to investigate whether the back-flow of urine into the caeca benefits the nitrogen economy of adult cockerels fed on a diet containing 100 g protein/kg and when dietary urea is absorbed, excreted into urine and utilised. 2. No significant effects of colostomy on nitrogen utilisation were observed in chickens fed on 100 g/kg protein diet, whereas colostomy was highly effective in decreasing it in chickens on a diet containing 50 g protein/kg plus urea (P < 0.05). 3. Nitrogen utilisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
3
18
1
Order By: Relevance
“…Dietary urea is suggested to be utilized in chickens fed on a low protein diet by entering the ceca by way of urine which back-flows from the cloaca to the ceca and being hydrolyzed in the ceca by micro-organisms (KARASAWA, 1989;KARASAWA and MAEDA, 1994). The increase in urea excretion and the decrease in ammonia excretion by cecal lgation in the present study at least support the suggestion that dietary urea enters the ceca along with urine and is hydrolyzed there in chickens.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Dietary urea is suggested to be utilized in chickens fed on a low protein diet by entering the ceca by way of urine which back-flows from the cloaca to the ceca and being hydrolyzed in the ceca by micro-organisms (KARASAWA, 1989;KARASAWA and MAEDA, 1994). The increase in urea excretion and the decrease in ammonia excretion by cecal lgation in the present study at least support the suggestion that dietary urea enters the ceca along with urine and is hydrolyzed there in chickens.…”
Section: Resultssupporting
confidence: 66%
“…These results are aimilar to previous findings with chickens fed a 5% protein diet or a 5% protein diet plus urea . Blood urea concentration was remarkably increased by feeding of urea as reported previously in chickens fed a low protein diet (KARASAWA and MAEDA, 1994). This accumulation of urea in the blood suggests an absorption of deitary urea in the intact form from the small intestine in chickens fed a moderate protein diet, because the essential initiator of the urea cycle, carbamyl phosphate synthetase, is absent in the fowl (TAMIR and RATNER, 1963).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, creatinine in excreta was considered to be derived from urine. However, Karasawa and Maeda (1994) cannot be discussed whether intestinal bacteria in caecum influence the urinary creatinine or not. Chamruspollert et al (2002a) demonstrated that breast muscle creatine was affected by dietary arginine levels in broiler chicks.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the caeca in the utilisation of dietary urea was also supported by the observation that urine was prevented from entering the caeca by colostomy and that such surgical modification had resulted in a considerable increase in urea excretion, almost accounting for all of the increase in total nitrogen excretion from colostomised birds (Karasawa, 1989;Karasawa and Maeda, 1994). However, in these previous studies, where the urea had been fed with a low protein diet, the value desired for nitrogen utilisation represented the combined utilisation of urea nitrogen and protein nitrogen, because the proportion of excretory nitrogenous compounds derived from dietary urea was not determined.…”
Section: Introductionmentioning
confidence: 89%